Time of flight mass spectrometry of pharmaceutical systems - Armitage Nolan, Jennifer Claire (2013)
Time-of-flight secondary ion mass spectrometry (ToF-SIMS) is a widely used surface chemical analysis technique that is traditionally employed to characterise the first few molecular layers of a material interface. The ability of this technique to accurately reflect the surface chemistry of polymers, biomaterials and many other solid materials is well documented. However, the majority of research that utilises this technique is based upon a qualitative rather than quantitative assessment of the material under investigation. The qualitative analysis of a range of traditional tablet and bead formulations containing drug and multiple excipients was performed in order to identify key diagnostic ions for all the different components. The lateral distributions of the ions across the surfaces of these formulations were imaged. Two different methods were then used to perform a qualitative analysis of the surfaces and results from these experiments were compared to the bulk composition. The effect of surface roughness on the ability to produce reproducible quantitative analyses from ToF SIMS ion yield data was investigated. A range of samples with different topographies were studied including polytetrafluoroethylene (PTFE), glass microscope slides, gold coated abrasive papers and gold coated precision measurement samples. The surface roughness was assessed by Atomic Force Microscopy and Laser Profilometry. Samples were analysed in imaging mode and the variance in ionization across the total image was measured for each sample. Evidence is presented that there is a relationship between ion yield and surface roughness, and that the surface roughness of the analysed surfaces will effect on any quantification approach in the processing of ToF-SIMS data. In addition, the presence of any orientation/directionality in surface features also needs to be evaluated when considering use of a quantitative approach. To investigate the effect of chemical environment on the ability to derive quantitative data from ToF SIMS analysis of pharmaceutical materials, drug loaded spun cast polymer films with low surface roughness were studied. ToF SIMS data were obtained for two chemically similar drugs in two different polymer matrices. In the majority of the samples there was no quantitative relationship between drug ion intensity and nominal bulk composition. Due to the large sample set, the multivariate technique, Principal Component Analysis (PCA) was employed to look at variance in secondary ion yields from the different samples. PCA is becoming more prevalent in ToF-SIMS data interrogation as it allows for a mathematically un-biased analysis of sample variables through the identification of the ions that account for the majority of the variance in the sample set. PCA successfully highlighted the impact of the chemical environment, showing secondary ion yields of drugs can be dependent on the surrounding matrix. PCA was also used to look at variance in two of the tablet samples and was successfully able to differentiate between the tablet samples with the lowest and highest concentrations of paracetamol. This thesis has demonstrated that surface topography and surface chemical environment or matrix will have a significant impact on ion yields in the ToF-SIMS experiments. These findings suggest caution in the use of ToF-SIMS for the quantitative analysis of complex chemically heterogeneous and topographically diverse pharmaceutical formulations .